el-Mecelletü'l-Bartîkiyyetu's-Süryânîyye. - Ignatius Aphram I‏, Antakya Patriği, 1887-1957. (Piscataway, NJ)
2 cilt (1. c. x, 123 sayfa ; 2. c. 200, xii sayfa)
Keywords: “The History of Syriac Dioceses, by the late Patriarch Aphram I of Antioch and all the East, is a synopsis of a much larger study still in manuscript form. This selected portion of this history, published for the first time in English translation (volume 1) along with the original Arabic text (volume 2), offers the reader an in-depth treatment of the conditions of the Syrian Orthodox Church in the seventeenth and eighteenth centuries“ -- Yayıncı.